FC 130RANDOMIZED, PLACEBO-CONTROLLED, PHASE 3B TRIAL OF TOLVAPTAN IN THE TREATMENT OF CHILDREN AND ADOLESCENTS WITH AUTOSOMAL DOMINANT POLYCYSTIC KIDNEY DISEASE (ADPKD): 1-YEAR DATA. (29th May 2021) - Mekahli, Djalila; Guay-Woodford, Lisa; Cadnaparphornchai, Melissa; Greenbaum, Laurence A; Litwin, Mieczysław; Seeman, Tomas; Dandurand, Ann; Shi, Lily; Sikes, Kimberley; Shoaf, Susan; Schaefer, Franz
Abstract: Background and Aims: Tolvaptan (TOL) is a vasopressin V2 receptor antagonist that inhibits total kidney volume (TKV) growth and kidney function decline in adults with rapidly progressing ADPKD. The therapeutic potential of TOL in pediatric patients at risk of early disease progression has not been previously reported. We conducted a clinical trial of TOL in children and adolescents with early manifesting ADPKD to evaluate pharmacodynamic properties and preliminary efficacy and safety information in this age group. Method: This was a Phase 3b, 2-part trial (EudraCT: 2016-000187-42; ClinicalTrials.gov: NCT02964273). Phase A (reported here) was a 1-year, randomized, double-blind, placebo (PBO)-controlled, multicenter trial; Phase B is an ongoing, 2-year, open-label extension. Subjects had to be diagnosed with ADPKD (presence of renal cysts with family history and/or genetic diagnosis), with estimated glomerular filtration rate (eGFR) ≥60 mL/min/1.73 m2 and body weight ≥20 kg. The target population was aged 12-17 years; subjects aged 4-11 years were also allowed to enter if eligibility criteria were met. Starting and maintenance TOL/PBO doses were based on body weight. The co-primary endpoints were changes from baseline in spot urine osmolality (Uosm) and specific gravity at Week 1; additional endpoints were the 12-month changes in TKV and eGFR. Safety and tolerability were monitored. In this exploratory trial, outcomes were summarized descriptively, with no statistical comparisons planned between groups. Results: Of 91 subjects enrolled (66 aged 12–17 years and 25 aged <12 years), 48 were randomized to TOL and 43 to PBO. Among enrolled subjects, there was a history of hypertension in 23.1%, proteinuria 15.4%, kidney pain 12.1%, and hepatic cysts 6.6%. Mean changes (±SD) from baseline in spot Uosm and specific gravity at Week 1 were greater with TOL vs PBO: -386 (284) vs -93 (332) mOsm/kg and -0.009 (0.007) vs -0.002 (0.008), respectively. In subjects aged 12–17 years (1 subject with tuberous sclerosis and ADPKD excluded as an outlier), the mean % TKV change (±SD) from baseline to Month 12 was 4.6% (9.1) for TOL and 7.7% (9.3) for PBO (Figure 1 ). Mean change (±SD) in eGFR from Day 7 to Month 12 in subjects ages 12–17 years was 0.4 (10.3) mL/min/1.73 m2 for TOL and -3.5 (10.9) mL/min/1.73 m2 for PBO (Figure 2 ). The most frequent treatment-emergent adverse events during Phase A were (TOL vs PBO): polyuria (25.0% vs 2.3%), blood creatinine increased (18.8% vs 4.7%), pollakiuria (18.8% vs 0.0%), cough (14.6% vs 11.6%), nocturia (14.6% vs 4. 7%), thirst (14.6% vs 2.3%), abdominal pain (12.5% vs 7.0%), constipation (10.4% vs 2.3%), and orthostatic hypotension (10.4% vs 0.0%). Potentially clinically significant increases in creatinine (>1.5 x baseline) occurred in 4 TOL subjects and no PBO subject. No subject had elevated transaminases or drug-induced liver injury. Serious adverse events were reported in 1 TOL subject (viral pericarditis) and 6 PBO, none considered related to treatment. One subject discontinued due to pollakiuria (TOL) and 1 due to dizziness (PBO). Conclusion: TOL demonstrated activity indicative of effective V2 receptor antagonism in children and adolescents with ADPKD. In addition, our trial yielded preliminary results suggestive of efficacy in slowing TKV growth and eGFR decline with acceptable tolerability, warranting further investigation in pediatric patients with ADPKD. The 2-year, Phase B extension to this trial is ongoing. Sponsored by OPDC, Inc.